Why does this Juice Produce so Much Foam? (2019)
The question of "Why does lulo juice foam so much?" from the younger member of Pablo Correa's family arouses in him the interest in answering it, because no one in the family gave her answer when the girl made it, through a Twitter post she got hints of response that led her to be able to answer the little girl and reaffirm the reflection of listening and trying to answer everything to the children can think of it.